Preparation method and application of dimethyl ether carbonylation catalyst
By using mono-inorganic acids and polycarboxylic acids to prepare wet materials and preparing H-MOR molecular sieve catalysts through extrusion molding and other processes, the existing catalysts have been solved, the catalytic activity and stability have been significantly improved, and it is suitable for dimethyl ether carbonylation reaction.
Patent Information
- Application Number
- CN202411722469.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
AI Technical Summary
The existing dimethyl ether carbonylation catalysts have low catalytic activity and poor stability in the reaction, which limits their promotion and application in the commercial field.
The wet material is prepared by mono-inorganic acid and poly-carboxylic acid, and the molded H-MOR molecular sieve catalyst is prepared through extrusion, exchange, drying and calcining processes. This method improves the strength and diffusion capacity of the catalyst.
The catalytic activity and stability of the catalyst were significantly improved, and the catalytic activity improvement effect was shown in the dimethyl ether carbonylation reaction, and the catalytic activity and stability were both improved.
Smart Images

Figure BDA0005158521310000081 
Figure BDA0005158521310000091
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method of a dimethyl ether carbonylation catalyst and its application, belonging to the field of industrial catalysis. Background Art
[0002] Ethanol is an important basic chemical that is closely related to human life. Globally, about 66% of ethanol is used as a gasoline additive, namely fuel ethanol. Fuel ethanol can significantly improve the quality of gasoline and greatly reduce pollutants emitted by vehicles. As an environmentally friendly clean fuel, it has been widely recognized and promoted in countries around the world. In addition, ethanol can be converted into ethylene, a basic chemical raw material, through simple dehydration treatment, which is of great significance for promoting the development of the downstream fine chemical industry and reducing dependence on petroleum resources.
[0003] There are two main ways to produce ethanol from biomass hydrolysis and fermentation: one is to use agricultural products as fermentation raw materials, and the other is to use lignin and other materials as fermentation raw materials. At present, the most commonly used production method is to use agricultural products as raw materials for hydrolysis and fermentation to produce ethanol. For example, the United States mainly uses corn fermentation to produce ethanol, Brazil mainly uses sucrose fermentation, and China uses aged grain fermentation to produce ethanol. However, from the perspective of China's food security strategy of "not competing with others for food and not competing with food for land", it is not feasible to rely on agricultural product fermentation to meet the demand of the fuel ethanol market. In contrast, the second-generation fuel ethanol production technology using lignin as raw material is considered to be the most promising green production route because of its rich and widely available raw materials. However, due to limitations in technology level and production costs, this technology is still in the industrial demonstration stage and has not yet been applied in large-scale industrial production.
[0004] At present, the green ethanol synthesis route of synthesizing dimethyl ether (DME) from raw materials such as coal, biomass, and shale gas, then generating methyl acetate (MA) through carbonylation reaction, and finally hydrogenating methyl acetate to produce ethanol has broad industrial application prospects and has received widespread attention from the industry. In this process, the development of DME carbonylation catalysts with high activity and high stability is one of the key challenges faced. Although mordenite (H-MOR) shows certain activity in the carbonylation reaction of dimethyl ether, it has problems such as low catalytic activity and poor stability, which restrict its promotion and application in the commercial field. Summary of the invention
[0005] According to the first aspect of the present application, a method for preparing a dimethyl ether carbonylation catalyst is provided. The method uses a monobasic inorganic acid and a polybasic carboxylic acid to prepare a wet material, respectively, and then mixes the two together and kneads them, and then sequentially undergoes extrusion molding, exchange, drying, and roasting processes to finally obtain a molded H-MOR molecular sieve catalyst. The method is conducive to improving the strength and diffusion capacity of the catalyst. Good diffusion performance ensures that the reactants can quickly and fully contact the active center of the catalyst, and the product can be separated in time, avoiding the blockage and inhibition of the active center, so that the catalytic activity and stability of the catalyst during the reaction are improved.
[0006] A catalyst extrusion molding method, the method comprising the following steps:
[0007] S1, mixing Na-MOR molecular sieve raw powder I, a binder I, and an extrusion aid I, and then adding a monobasic inorganic acid, kneading I, to obtain a wet material I;
[0008] S2, mixing Na-MOR molecular sieve raw powder II, binder II, and extrusion aid II, and then adding polycarboxylic acid, kneading II, to obtain wet material II;
[0009] S3, mixing wet material I and wet material II into III, extruding into strips, and drying to obtain a shaped Na-MOR molecular sieve;
[0010] S4. exchanging, drying and calcining the formed Na-MOR molecular sieve to obtain a formed H-MOR molecular sieve catalyst.
[0011] Optionally, in step S1, the monobasic inorganic acid is selected from at least one of nitric acid and hydrochloric acid.
[0012] Optionally, the mass concentration of the monobasic inorganic acid is 5% to 20%.
[0013] Optionally, in step S2, the polycarboxylic acid is selected from at least one of citric acid, oxalic acid, malonic acid and tartaric acid.
[0014] Optionally, the mass concentration of the polycarboxylic acid is 5% to 20%.
[0015] Optionally, in steps S1 and S2, the binder I and the binder II are independently selected from at least one of aluminum hydroxide, aluminum sol, and pseudo-boehmite;
[0016] The extrusion aid I and the extrusion aid II are independently selected from at least one of paraffin powder, methyl cellulose, starch, sesbania powder and glucose.
[0017] Optionally, in step S1, the mass ratio of Na-MOR molecular sieve raw powder I, binder I, extrusion aid I, and monobasic inorganic acid is 100:10-40:1-5:30-60.
[0018] Optionally, in step S2, the mass ratio of Na-MOR molecular sieve raw powder I, binder I, extrusion aid I, and polycarboxylic acid is 100:10-40:1-5:30-60.
[0019] Optionally, in step S3, the mass ratio of wet material I to wet material II is 1:1-3.
[0020] Optionally, in steps S1 and S2, the mixing time of mixing material I and mixing material II is independently 0.5 to 5 hours.
[0021] Optionally, in steps S1, S2 and S3, the time for kneading I, kneading II and kneading III is independently 0.5 to 5 hours.
[0022] Optionally, the H-MOR molecular sieve has a silicon to aluminum ratio of 5-50.
[0023] According to a second aspect of the present application, there is provided a use of the molded H-MOR molecular sieve catalyst obtained by the above method in carbonylation of dimethyl ether to produce methyl acetate.
[0024] The molded H-MOR molecular sieve catalyst obtained by the method described above is used in the carbonylation of dimethyl ether to produce methyl acetate.
[0025] The shaped H-MOR molecular sieve catalyst prepared by the above method has improved catalytic activity and stability in the reaction of carbonylation of dimethyl ether to produce methyl acetate.
[0026] The beneficial effects of this application include:
[0027] The preparation method and application of the dimethyl ether carbonylation catalyst provided in the present application are conducive to improving the strength and diffusion capacity of the catalyst, so that the catalytic activity and stability of the catalyst are improved during the reaction. The obtained catalyst exhibits an excellent catalytic activity improvement effect in the dimethyl ether carbonylation reaction, and both the catalytic activity and stability are improved. DETAILED DESCRIPTION
[0028] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0029] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.
[0030] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0031] The silicon-aluminum ratio of H-MOR molecular sieve is 20.
[0032] In the examples, the concentrations of monobasic inorganic acids and polybasic carboxylic acids are all mass concentrations.
[0033] The analysis method in the examples of this application is as follows:
[0034] Strength test of catalyst: The radial compressive strength of catalyst particles is measured according to the provisions of HG / T2782, where the intelligent particle strength testing machine has a range of 0N-250N, the sample diameter is 3-3.5mm, the strip length is 3-5mm, both end surfaces are polished, and the number of particles measured in the sample is 40.
[0035] Diffusion performance test of the catalyst: The dimethyl ether adsorption experiment was carried out on a Mettler-Toledo thermogravimetric analyzer (TGA / DSC3+). The sample (about 30 mg) was dehydrated under high vacuum conditions at 350°C for 6 hours before testing. Then, the sample was transferred to the thermogravimetric analyzer and stabilized at 50°C, and then dimethyl ether (5.0 v% DME balanced in Ar) was introduced into the system for adsorption.
[0036] Product analysis: carried out on a Fuli GC9790 gas chromatograph, HP-PLOT / Q column, FID detector; dimethyl ether (DME) conversion rate and methyl acetate (MA) selectivity data were uniformly calculated by the area normalization method.
[0037] In the examples of this application, the conversion rate and selectivity are calculated as follows:
[0038] In the examples and comparative examples, the conversion of dimethyl ether (DME) and the selectivity of methyl acetate (MA) are calculated based on the carbon molar number of dimethyl ether:
[0039] Dimethyl ether conversion rate = [(molar number of dimethyl ether carbon in the feed gas) - (molar number of dimethyl ether carbon in the product)] ÷ (molar number of dimethyl ether carbon in the feed gas) × (100%);
[0040] Methyl acetate selectivity = (2 / 3) × (the number of moles of carbon of methyl acetate in the product) ÷ [(the number of moles of carbon of dimethyl ether in the feed gas) - (the number of moles of carbon of dimethyl ether in the product)] × (100%).
[0041] Example 1
[0042] (1) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% nitric acid was added and kneaded for 0.5 h to obtain wet material I;
[0043] (2) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% citric acid was added and kneaded for 0.5 h to obtain wet material II;
[0044] (3) The wet materials obtained in (1) and (2) were kneaded for 0.5 h, extruded into strips, and dried at 120° C. for 6 h to obtain a shaped Na-MOR molecular sieve.
[0045] At 80°C, the formed Na-MOR molecular sieve was exchanged with nitric acid solution for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the ion exchange 3 times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 500°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0046] Example 2
[0047] The operation is the same as that in Example 1, except that only nitric acid is replaced by hydrochloric acid and citric acid is replaced by oxalic acid to obtain a formed Na-MOR molecular sieve.
[0048] At 80°C, the formed Na-MOR molecular sieve and sulfuric acid solution were exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0049] Example 3
[0050] The operation is the same as in Example 1, except that only citric acid is replaced by oxalic acid to obtain a formed Na-MOR molecular sieve.
[0051] At 80°C, the formed Na-MOR molecular sieve and ammonium sulfate solution were exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 550°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0052] Example 4
[0053] The operation is the same as in Example 1, except that only nitric acid is replaced by hydrochloric acid to obtain a formed Na-MOR molecular sieve.
[0054] At 80°C, the formed Na-MOR molecular sieve and ammonium nitrate solution were exchanged for 3 hours (the concentration of the ammonium nitrate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the ion exchange 3 times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 500°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0055] Example 5
[0056] The operation is the same as in Example 1, except that only citric acid is replaced by malonic acid to obtain a formed Na-MOR molecular sieve.
[0057] At 80°C, the formed Na-MOR molecular sieve and sulfuric acid solution were ion exchanged for 3 hours (the concentration of sulfuric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 550°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0058] Example 6
[0059] The operation is the same as that in Example 1, except that only nitric acid is replaced by hydrochloric acid and citric acid is replaced by malonic acid to obtain a formed Na-MOR molecular sieve.
[0060] At 80°C, the formed Na-MOR molecular sieve and nitric acid solution were exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0061] Comparative Example 1
[0062] (1) 100 g of Na-MOR molecular sieve powder, 30 g of pseudo-boehmite, and 2 g of paraffin powder were mixed for 1 hour, and then 50 g of 15% nitric acid was added and kneaded for 1 hour to obtain a wet material;
[0063] (2) The obtained wet material is extruded into strips and dried at 120° C. for 6 hours to obtain a shaped Na-MOR molecular sieve.
[0064] At 80°C, the formed Na-MOR molecular sieve and ammonium nitrate solution were exchanged for 3 hours (the concentration of the ammonium nitrate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0065] Comparative Example 2
[0066] (1) 100 g of Na-MOR molecular sieve powder, 30 g of pseudo-boehmite, and 2 g of paraffin powder were mixed for 1 hour, and then 50 g of 15% citric acid was added and kneaded for 1 hour to obtain a wet material;
[0067] (2) The obtained wet material is extruded into strips and dried at 120° C. for 6 hours to obtain a shaped Na-MOR molecular sieve.
[0068] At 80°C, the formed Na-MOR molecular sieve and nitric acid solution were exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0069] Comparative Example 3
[0070] (1) 100 g of Na-MOR molecular sieve powder, 30 g of pseudo-boehmite, and 2 g of paraffin powder were mixed for 1 hour, and then 25 g of 15% nitric acid and 25 g of 15% citric acid were added and kneaded for 1 hour to obtain a wet material;
[0071] (2) The obtained wet material is extruded into strips and dried at 120° C. for 6 hours to obtain a shaped Na-MOR molecular sieve.
[0072] At 80°C, the formed Na-MOR molecular sieve and ammonium sulfate solution were exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0073] Comparative Example 4
[0074] (1) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% nitric acid was added and kneaded for 0.5 h to obtain wet material I;
[0075] (2) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% acetic acid was added and kneaded for 0.5 h to obtain wet material II;
[0076] (3) The wet materials obtained in (1) and (2) were kneaded for 0.5 h, extruded into strips, and dried at 120° C. for 6 h to obtain a shaped Na-MOR molecular sieve.
[0077] At 80°C, the formed Na-MOR molecular sieve and ammonium sulfate solution were exchanged for 3 hours (the concentration of ammonium sulfate solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0078] Comparative Example 5
[0079] (1) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% phosphoric acid was added and kneaded for 0.5 h to obtain wet material I;
[0080] (2) 50 g of Na-MOR molecular sieve powder, 15 g of pseudo-boehmite, and 1 g of paraffin powder were mixed for 0.5 h, and then 25 g of 15% citric acid was added and kneaded for 0.5 h to obtain wet material II;
[0081] (3) The wet materials obtained in (1) and (2) were kneaded for 0.5 h, extruded into strips, and dried at 120° C. for 6 h to obtain a shaped Na-MOR molecular sieve.
[0082] At 80°C, the formed Na-MOR molecular sieve and nitric acid solution were exchanged for 3 hours (the concentration of the nitric acid solution was 1 mol / L, and the solid-liquid mass ratio was 1:8). After repeating the exchange three times, it was dried at 120°C for 12 hours, heated at 3°C / min in a muffle furnace, and calcined at 600°C for 6 hours to obtain a formed H-MOR molecular sieve catalyst.
[0083] Catalyst strength test:
[0084] The strength of the molded H-MOR molecular sieve catalysts of Examples 1 and 2 and Comparative Examples 1 and 4 was tested, as shown in Table 1, and it can be seen that the strength of Examples 1 and 2 is significantly higher than that of Comparative Examples 1 and 4. This indicates that the extrusion molding method of the present application, which uses a monobasic inorganic acid and a polybasic carboxylic acid to prepare a wet material and then mixes it, can significantly improve the strength of the catalyst.
[0085] Table 1
[0086] Example / Comparative Example Average radial compressive strength of catalyst particles (N / cm) Example 1 110 Example 2 105 Comparative Example 1 78 Comparative Example 4 60
[0087] Catalyst diffusion performance test:
[0088] The diffusion performance of the molded H-MOR molecular sieve catalysts of Examples 1 and 3 and Comparative Examples 3 and 5 was tested, as shown in Table 2. It can be seen that the weight gain after equilibrium of Examples 1 and 3 is significantly higher than that of Comparative Examples 3 and 5, and the adsorption equilibrium time of Examples 1 and 3 is significantly lower than that of Comparative Examples 3 and 5. This shows that the extrusion molding method of the present application, which uses a monobasic inorganic acid and a polybasic carboxylic acid to prepare a wet material and then mixes it, can significantly improve the diffusion performance of the catalyst.
[0089] Table 2
[0090]
[0091]
[0092] Evaluation of carbonylation of dimethyl ether to produce methyl acetate:
[0093] The H-MOR molecular sieve obtained in the above examples and comparative examples was used as a catalyst. The activity evaluation was carried out at a temperature of 190°C and a pressure of 2.0 MPa. The feed volume ratio DME:N2:CO was 1:13:7, and the volume space velocity was 1800 h -1 The operation was continued, and the reaction results were detected after 50 h and 200 h, as shown in Table 3.
[0094] Table 3
[0095] Example / Comparative Example 50h, DME conversion rate / % 200h, DME conversion rate / % Example 1 82 75 Example 2 80 74 Example 3 81 75 Example 4 83 77 Example 5 86 76 Example 6 80 73 Comparative Example 1 68 52 Comparative Example 2 71 54 Comparative Example 3 67 52 Comparative Example 4 68 51 Comparative Example 5 65 49
[0096] Note: MA selectivity is greater than 99%.
[0097] As shown in Table 3, in Examples 1-6, the catalysts obtained by the extrusion molding method of preparing wet materials with monobasic inorganic acid and polycarboxylic acid and then mixing them, after running for 50 hours, the DME conversion rate was above 80%, and after running for 200 hours, the DME conversion rate did not decrease significantly, and always maintained above 73%. Comparative Example 1 is to prepare wet materials with only nitric acid in one step, Comparative Example 2 is to prepare wet materials with only citric acid in one step, Comparative Example 3 is to prepare wet materials with mixed acid in only one step, Comparative Example 4 is to prepare wet materials with acetic acid, and Comparative Example 5 is to prepare wet materials with phosphoric acid. After running for 50 hours, the DME conversion rate was about 70%, and after running for 200 hours, the DME conversion rate dropped significantly to about 50%.
[0098] In summary, the extrusion molding method of the present application, which uses a monobasic inorganic acid and a polybasic carboxylic acid to prepare a wet material and then mixes it, can significantly improve the strength of the catalyst and the diffusion performance of the catalyst. It shows an excellent catalytic activity improvement effect in the dimethyl ether carbonylation reaction, and both the catalytic activity and stability are improved.
[0099] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a dimethyl ether carbonylation catalyst, characterized in that: The method comprises the following steps: S1, mixing Na-MOR molecular sieve raw powder I, a binder I, and an extrusion aid I, and then adding a monobasic inorganic acid, kneading I, to obtain a wet material I; S2, mixing Na-MOR molecular sieve raw powder II, binder II, and extrusion aid II, and then adding polycarboxylic acid, kneading II, to obtain wet material II; S3, mixing wet material I and wet material II into III, extruding into strips, and drying to obtain a shaped Na-MOR molecular sieve; S4. exchanging, drying and calcining the formed Na-MOR molecular sieve to obtain a formed H-MOR molecular sieve catalyst.
2. The method according to claim 1, characterized in that In step S1, the monobasic inorganic acid is selected from at least one of nitric acid and hydrochloric acid; Preferably, the mass concentration of the monobasic inorganic acid is 5% to 20%.
3. The method according to claim 1, characterized in that In step S2, the polycarboxylic acid is selected from at least one of citric acid, oxalic acid, malonic acid, and tartaric acid; Preferably, the mass concentration of the polycarboxylic acid is 5% to 20%.
4. The method according to claim 1, characterized in that: In steps S1 and S2, the binder I and the binder II are independently selected from at least one of aluminum hydroxide, aluminum sol, and pseudo-boehmite; The extrusion aid I and the extrusion aid II are independently selected from at least one of paraffin powder, methyl cellulose, starch, sesbania powder and glucose.
5. The method according to claim 1, characterized in that In step S1, the mass ratio of Na-MOR molecular sieve raw powder I, binder I, extrusion aid I, and monobasic inorganic acid is 100:10-40:1-5:30-60.
6. The method according to claim 1, characterized in that In step S2, the mass ratio of Na-MOR molecular sieve raw powder I, binder I, extrusion aid I, and polycarboxylic acid is 100:10-40:1-5:30-60.
7. The method according to claim 1, characterized in that In step S3, the mass ratio of wet material I to wet material II is 1:1-3.
8. The method according to claim 1, characterized in that: In steps S1 and S2, the mixing time of mixing material I and mixing material II is independently 0.5 to 5 hours.
9. The method according to claim 1, characterized in that: In steps S1, S2 and S3, the time of mixing I, mixing II and mixing III is independently 0.5 to 5 hours.
10. Use of the shaped H-MOR molecular sieve catalyst obtained by the method according to any one of claims 1 to 9 in the carbonylation of dimethyl ether to produce methyl acetate.